Self-care behaviours mediate the effect of educational intervention on health-related quality of life of patients with heart failure: causal mediation analysis. (14th October 2021) - Hwang, B; Yu, H; Jeong, Y; Cho, H.-J; Lee, H.-Y
Abstract: Background/Introduction: Educational interventions have been developed and tested in an attempt to improve health-related quality of life (HRQOL) for patients with heart failure (HF). While some have shown satisfactory results, the mechanism of the intervention effect on HRQOL remains unclear. Purpose: To explore whether HF knowledge, self-care behaviours, self-care maintenance, self-care confidence, or social support mediates the effect of intervention on HRQOL of patients with HF Methods: We analysed data from a randomized controlled trial testing the effect of an educational intervention for patients with HF. The intervention group (n=60) received 1-hour single session education followed by 8-week telephone follow-ups, and the control group (n=62) received care as usual. Study variables were measured at baseline and at 3 and 6 months. Using causal mediation analysis described by Valeri & VanderWeele (2013), we explored the causal pathway between intervention allocation and HRQOL at 6 months with HF knowledge, self-care behaviours, self-care maintenance, self-care confidence, and social support measured at 3 months as potential mediators (Figure 1). Results: Intervention allocation was significantly associated with HF knowledge, self-care behaviours, self-care maintenance, and self-care confidence at 3 months (all p<0.05), but not with social support at 3 months (p=0.57). In unadjusted models, none of the potential mediators had a significant indirect effect between intervention and HRQOL. When adjusting for age and gender, the indirect effect of self-care behaviours on 6-month HRQOL became significant (indirect effect −6.24, 95% CI: −12.88 to −1.18). When baseline values of the mediator and HRQOL were adjusted in addition to age and gender, the indirect effect of self-care behaviours remained significant (indirect effect −7.18, 95% CI: −13.48 to −2.35) and the indirect effect of self-care maintenance became significant (indirect effect −3.02, 95% CI: −7.94 to −0.07). Conclusion: Our findings support the mediating role of self-care behaviours on the relationship between the educational intervention and HRQOL of patients with HF. In order to successfully improve HRQOL of patients with HF, educational interventions should aim to promote self-care behaviours, especially by encouraging treatment adherence and self-monitoring. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Seoul National University, College of Medicine